Forced Defense (Noodweer) in Sexual Violence Crimes - Andi Nurwiratma Akzanti; Mulyati Pawennei; Andi Cakra Cindrapole (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to determine and analyze whether the application of criminal law from the perpetrator of forced defense in decision no. 1 / Pid.Sus-Anak / 2020 / PN Kpn.This study uses a Normative research method, namely discussing the legal materials that have been obtained by referring to the existing theoretical basis.The results of this study indicate the results of the judge's decision that the legal fact was not revealed that the defendant committed his actions under duress to defend himself or others as regulated in Article 49 of the Criminal Code and the defendant was charged with Article 351 Paragraph 3 of the Criminal Code.The recommendation of this study refers to the consideration of the judge as a law enforcer, to pay more attention to everyone who carries out a forced defense, in the event of a criminal act, the perpetrator of the forced defense can bravely explain the actual incident to the person concerned, namely the police as law enforcer for the actions committed.